2013
DOI: 10.1016/j.celrep.2013.05.029
|View full text |Cite
|
Sign up to set email alerts
|

SOX2 Regulates YAP1 to Maintain Stemness and Determine Cell Fate in the Osteo-Adipo Lineage

Abstract: SUMMARY The osteoblastic and adipocytic lineages arise from mesenchymal stem cells (MSCs), but few regulators of self-renewal and early cell-fate decisions are known. Here, we show that the Hippo pathway effector YAP1 is a direct target of SOX2 and can compensate for the self-renewal defect caused by SOX2 inactivation in osteoprogenitors and MSCs. Osteogenesis is blocked by high SOX2 or YAP1, accelerated by depletion of either one, and the inhibition of osteogenesis by SOX2 requires YAP1. SOX2 favors adipogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
199
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(215 citation statements)
references
References 49 publications
13
199
2
1
Order By: Relevance
“…Like cysts in humans with ADPKD (35), kidney cysts in Taz null mice display enhanced Wnt/␤-catenin signaling (65). This provides evidence of cross talk between Wnt and Hippo signaling pathways that has been further validated in other model systems such as colorectal carcinoma and in osteogenesis (30,58). It also provides a potential mechanistic explanation for cyst formation in Taz-null mice.…”
Section: Tubules and Interstitiummentioning
confidence: 77%
“…Like cysts in humans with ADPKD (35), kidney cysts in Taz null mice display enhanced Wnt/␤-catenin signaling (65). This provides evidence of cross talk between Wnt and Hippo signaling pathways that has been further validated in other model systems such as colorectal carcinoma and in osteogenesis (30,58). It also provides a potential mechanistic explanation for cyst formation in Taz-null mice.…”
Section: Tubules and Interstitiummentioning
confidence: 77%
“…Konsavage et al have reported that β-catenin drives Yap transcription in colorectal cancer cells (35). Yap is also a target of SOX2 and binds β-catenin, thus indirectly dampening Wnt signals that regulate osteoblastic and adipocytic stem cell lineages (36). Given the complexity of the cross-talk between Yap and β-catenin, we did not further examine the mechanism underlying the regulation of β-catenin by Yap in GC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Also in the postnatal (3-week-old) pituitary, nuclear localization of YAP1 and TAZ was observed in the SOX2 + stem cell niche, and some signals were found scattered in the parenchyma (Lodge et al 2016). As SOX2 has been suggested to exert a stimulatory effect on YAP/TAZ activity in other tissues, directly by promoting Yap1 gene transcription (Seo et al 2013) and indirectly by repressing the Hippo pathway activators neurofibromin 2 (Nf2) and WW domaincontaining protein 1 (Wwc1) (Basu-Roy et al 2015), an upstream regulatory function of SOX2 in the Hippo cascade may also be assumed in the pituitary (stem cells), although this connection has still to be explored.…”
Section: Hippo Pathway: a New Player In Pituitary Stem Cell Regulation?mentioning
confidence: 93%